Workplace mobbing - Selič, Polona (Obzornik zdravstvene nege, 2012)
Introduction: Mobbing in the workplace is defined as any systematic maltreatment of employees against a colleague (horizontal mobbing), a subordinate (downward mobbing) or a superior (upward mobbing). Employees in health care sector are often faced with mobbing due to unclearly defined tasksand expectations and the extant health care vertical hierarchical organizational structure. The aim of research is to establish the prevalence and nature of mobbing events among physicians and nurses, addressing the extent to which demographic issues are pertinent to the workplace mobbing. Methods: Translated and adopted the Leymann Inventory of Psychological Terrorization questionnaire was used, including questions about the respondentsć demographics, psychosomatic implications of mobbing, sick leave, length of work experience, and educational status of perpetrators. Of the 200 questionnaires distributed, 161 were returned (response rate = 80.5 %). Participating in the study were 84 (52.2 %) physicians (every second) and 77 (47.8 %) nurses (every eighth) who had been employed in the Celje General Hospital for more than six months, representing a systematic sample. The participation was voluntary and anonymity assured. Results: The incidence of exposure to mobbing among physicians and nurses was high (60.1 %) but comparable to the results of other studies. A higher percentage of nurses (71.4 %) as compared to physicians (51.2 %) were exposed to mobbing (p = 0,009). In both cases, the perpetrators were mainly superiors and most frequent mobbing behavior towards victims was prohibiting of communication. Discussion and conclusions: As a result of mobbing, the victims from both healthcare groups developed different psychological and physical health problems. Hospital executives should therefore adopt zero-tolerance policy towards workplace mobbing, take effective preventive measures to eliminate mobbing behaviour and apply appropriate sanctions to perpetrators.
Keywords: medicinske sestre; nurses; perpetrator; physicians; trpinčenje na delovnem mestu; victim; workplace mobbing; zdravniki